2016
DOI: 10.1111/maec.12357
|View full text |Cite
|
Sign up to set email alerts
|

Highly restricted gene flow between disjunct populations of the skunk clownfish (Amphiprion akallopisos) in the Indian Ocean

Abstract: The skunk clownfish (Amphiprion akallopisos) has a disjunct distribution, occurring in the Eastern Indian Ocean (EIO) and the Western Indian Ocean (WIO), separated by several thousands of kilometres. Information on connectivity of marine species is very important for the correct spacing of marine protected areas, a powerful instrument for the protection of coral reefs. The population genetic structure of A. akallopisos was analysed in order to investigate connectivity amongst populations and to explain the dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 78 publications
4
27
0
Order By: Relevance
“…The first hierarchical grouping shows that the WIO populations are genetically distinct from the EIO populations, suggesting a WIO-EIO divide. This break within the Indian Ocean was also observed in the giant clams Tridacna maxima and Tridacna squamosa [73], the anemonefish Amphiprion akallopisos [58], the crown-of-thorns sea star Acanthaster planci [74], and the black tiger prawn Penaeus monodon [50, 66]. The limited genetic exchange between the WIO and EIO supports the notion that fewer islands exist in the Indian Ocean compared to the West Pacific in order to facilitate dispersal through “island hopping”.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…The first hierarchical grouping shows that the WIO populations are genetically distinct from the EIO populations, suggesting a WIO-EIO divide. This break within the Indian Ocean was also observed in the giant clams Tridacna maxima and Tridacna squamosa [73], the anemonefish Amphiprion akallopisos [58], the crown-of-thorns sea star Acanthaster planci [74], and the black tiger prawn Penaeus monodon [50, 66]. The limited genetic exchange between the WIO and EIO supports the notion that fewer islands exist in the Indian Ocean compared to the West Pacific in order to facilitate dispersal through “island hopping”.…”
Section: Discussionmentioning
confidence: 65%
“…Population expansion after a population bottleneck has also been observed in the IMPA populations of L . laevigata [14, 34, 57] and in other species in the WIO, such as the anemonefish Amphiprion akallopisos [58], mangrove crab Neosarmatium meinerti [53], fiddler crab Uca annulipes [51], mud crab Scylla serrata [59], and giant tiger prawn Penaeus monodon [50]. …”
Section: Discussionmentioning
confidence: 99%
“…We found that there is a significant congruence of patterns of genetic differentiation among species and that the Maldives (western/central Indian Ocean) represents a location of overlap or possible hybridization among distinct anemone populations or lineages (Sheppard et al, ). Previous studies have reported genetic discontinuity between the eastern and western Indian Ocean in different taxa including coral reef fishes (Bay, Choat, van Herwerden, & Robertson, ; Gaither et al, ; Huyghe & Kochzius, ; Leray et al, ) and invertebrates such as echinoderms (Otwoma & Kochzius, ; Vogler et al, ) and giant clams (Hui et al, ). Only one of these included samples from the Maldives (Vogler et al, ) and did not report overlap of different clades at these islands.…”
Section: Discussionmentioning
confidence: 99%
“…Many marine species are endemic to the Indo‐Pacific region and some of these have evolved symbiotic relationships, such as the iconic association between host sea anemones (Order Actiniaria) and anemonefishes (Genera Amphiprion and Premnas ; Fautin & Allen, ; Allen, Drew, & Fenner, ). A number of studies report large‐scale population genetic structure of anemonefishes (Dohna, Timm, Hamid, & Kochzius, ; Huyghe & Kochzius, ; Nanninga et al, ; O'Donnell, Beldade, Mills, Williams, & Bernardi, ; Saenz‐Agudelo et al, ; Steinberg et al, ; Timm & Kochzius, ). In general these studies indicate that anemonefish species such as Amphiprion bicinctus , Amphiprion ocellaris and Amphiprion perideraion display genetic structure that coincides with historical geographical barriers such as the Sunda shelf, the Straight of Bab Al Mandeb, between basins (Pacific Ocean and Indian Ocean) or between the eastern and western sides of the Indian Ocean.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation